Accessibility tools and resources: A reminder to create inclusive content. Issue 12 (16th August 2021) - Talarico, Donna
Abstract : When you're creating social media graphics, downloadable lead magnets, new academic program pages for your website, and email newsletters, are you keeping accessibility in mind? I certainly hope so. It's not only required by federal law for many colleges and universities, but it's simply the right thing to do — and will most likely lead to a better experience for all, not just for students with disabilities.